Comparison of clinical outcome between computed tomography-based image-guided brachytherapy and two-dimensional-based brachytherapy for cervical cancer - Nobuki Imano; Koichi Wadasaki; Ikuno Nishibuchi; Yasushi Nagata (Elsevier, 2019)
This study aimed to analyze the clinical results of radiotherapy for cervical cancer using two-dimensional (2D) intracavitary brachytherapy (ICBT) and computed tomography (CT)-based image-guided brachytherapy (IGBT) at our institution. Patients with stage IB-IVA cervical cancer who received ICBT between April 2008 and April 2014 were included in this study. In total 58 patients were assessed. The first 38 patients received ICBT with the 2D treatment plan (the 2D group), and the remaining 20 patients received CT-based IGBT (the IGBT group). The dose of point A tended to be lower in the IGBT group (mean value, 60.6 Gy vs. 62.5 Gy; p = .07), though the minimum dose to the 90% (D90) of the clinical target volume (CTV) was equivalent in both groups (mean value, 66.0 Gy vs. 66.2 Gy; p = .91). The rectum minimum dose to 2 cc (D2cc) was significantly lower in the IGBT group than in the 2D group (mean value, 61.2 Gy vs. 69.1 Gy; p = .001). With a median follow-up time of 60 months, the 5-year local control rates (LCRs) of the IGBT group and 2D group were 100% and 83%, respectively (p = .12). The 5-year incidence of rectal complications in the IGBT group and the 2D group were 11% and 29%, respectively (p = .26). Our study showed favorable LCR and preferred incidence of rectal complications in patients treated with CT-based IGBT. Keywords: Cervical cancer, Image-guided brachytherapy, CT-based IGBT, Rectal complications